Impact of non-cystic fibrosis bronchiectasis on critically ill patients in Korea: a retrospective observational study - Youngmok Park (Nature Portfolio, 2021)
Abstract This study investigated the impact of bronchiectasis on patients admitted to the intensive care unit (ICU) at a hospital in Korea. Patients with bronchiectasis were diagnosed using results of chest computed tomography performed before ICU admission. The severity of bronchiectasis was based on the number of affected lobes, and patients with ≥ 3 bronchiectatic lobes were classified into the severe bronchiectasis group. Overall, 823 patients were enrolled. The mean age was 66.0 ± 13.9 years, and 63.4% were men. Bronchiectasis and severe bronchiectasis were present in 148 (18.0%) and 108 (13.1%) patients, respectively. The increase in the number of bronchiectatic lobes was related to the rise in ICU mortality (P for trend = 0.012) and in-hospital mortality (P for trend = 0.004). Patients with severe bronchiectasis had higher odds for 28-day mortality [odds ratio (OR) 1.122, 95% confidence interval (CI) 1.024–1.230], ICU mortality (OR 1.119, 95% CI 1.023–1.223), and in-hospital mortality (OR 1.208, 95% CI 1.092–1.337). The severe bronchiectasis group showed lower overall survival (log-rank P < 0.001), and the adjusted hazard ratio was 1.535 (95% CI 1.178–2.001). Severe bronchiectasis had a negative impact on all-cause mortality during ICU and hospital stays, resulting in a lower survival rate.